The mutual friend : a novel - Bays, Carter, 1975- (Dutton, 2022)
"New York, 2015: The city is facing a series of bicycle accidents, the Mayor's approval ratings hang in the balance, and Alice, besieged by grief and regrets, wants desperately to take the MCAT and become a doctor, but she can't seem to sign up for the test. First and foremost there's her phone--which, like so many others, she can't seem to put down--but there's also her chaotic roommate Roxy, who works at the Mayor's office and whose thirst for adventure frequently gets Alice in trouble. Then there's her tech millionaire brother who is searching for meaning ... meaning which may threaten to take him away from his wife, Pitterpat. And finally, the biggest distraction of all: Love. As the months go by, these characters, and more, slide in and out of each other's lives--they fall in--and--out of love, and they face various scandals. All the while, their mutual friend, the omniscient and mysterious narrator of the novel who seems to know all, watches over them, until the threads that tie these characters together come together in a wholly satisfying reveal. Filled with all of the warmth, humor, and heart that gained How I Met Your Mother its cult following, The Mutual Friend completely captures the choreography of navigating life and love in the chaos of contemporary life"--